Negative infl uence of internet on the conduct studies in higher education - L. B. Ershteyn (Открытое образование (Москва), 2016)
The paper shows that nowadays the Internet is increasingly used in higher education. It is argued that the main directions of research use the Internet show a positive effect of using a global network of higher education. It was revealed that in addition to the positive influence of the Internet network has a signifi cant negative impact. Identifi ed such negative factors as the widespread learning task solving and quick copying in the case of the emergence of new jobs. Not shown the ability to publish new textbooks in applying active methods lectures, due to these facilities benefi ts the Internet. The prevalence of false information on the Internet. The question of providing students with the information as it is fi nished, it is shown that in some cases it is not advisable to do. It is said that the publication of the full study guides is suitable only in the case when it comes to the basic disciplines, in other cases it is doubtful. Analyzed the shortcomings of such methods of struggle with the designated program to identify factors such as plagiarism, limiting the exchange of scientifi c and methodological experience. Revealed such disadvantages of using plagiarism detection software as programs to combat the use of these programs, and others. It is shown that the use of new teaching jobs, may lead to the fact that completed assignments will be distributed by students via the Internet, and thus the depreciation of these tasks will occur. Revealed the following pattern of use of new teaching jobs in higher education: the more effective is the learning task, the greater the likelihood that it will be devalued. The question required a waiver of such types of learning tasks as translation work, which is due to the fact that students are copying term papers or materials to them without even reading them. The ways of using reports and abstracts that allow overcome the negative trend. It is shown that the use of the Internet actually blocks the exchange of scientifi c and methodological experience. Having analyzed the relevant use of the Internet in higher education some didactic principles. It is shown that the use of the Internet is contrary to this principle as a selflearning, so that students copy information even acquainted with its content. The principle of science, because the Internet is full of inaccurate, false information. Principle strength assimilation of knowledge, because the copy and sometimes not even scanned information is assimilated in any way. We offer ways to overcome the impact of these factors. It argued the need for specific additional studies designed to identify ways to combat negative trends of using the Internet in higher education and compliance of the use of the basic principles of didactics.